A polymeric protein-loaded microsphere delivery system for use in bone tissue engineering - Boukari, Yamina (2017)
The bone graft procedure is the gold standard therapy for large bone defects and usually involves implanting autologous bone into the defect site. The need to find more patient-friendly alternatives to the bone graft procedure is a driving force behind recent advances in bone tissue engineering. Different synthetic and natural biomaterials are being investigated for their use in the repair of large bone defects. However, there is still a need for scaffold materials that are able to sinter in situ with the capability of delivering growth factors that promote the bone repair process with minimal invasion.